2005
DOI: 10.1080/02652030500133768
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of various assays used for detection of beta-lactam antibiotics in poultry meat

Abstract: In this study, microbiological tests for the detection of beta-lactam antibiotics in meat and meat products were evaluated. The traditional FPT (four plate test, containing Bacillus subtilis and Kocuria rhizophila), BsDA (Bacillus stearothermophilus disc assay) and a newly developed microbiological test, Premi Test (containing Bacillus stearothermophilus) were included in the study. The limit of detection (LOD) of the Premi Test was compared with the LOD of the traditional methods. The detection limits of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 6 publications
3
24
0
Order By: Relevance
“…Therefore, this study has demonstrated the capability of Premi Õ Test to detect samples at the MRL level for sulphonamides and beta-lactams, but not for tetracyclines. These conclusions have confirmed the results of different teams over recent years (Reybroeck 2000a,b;Okerman et al 2004;Popelka et al 2005). Table 7 presented the combined results of a previous study carried out in 2003 and 2004 (64 samples actually containing antimicrobial residues) with the pilot study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, this study has demonstrated the capability of Premi Õ Test to detect samples at the MRL level for sulphonamides and beta-lactams, but not for tetracyclines. These conclusions have confirmed the results of different teams over recent years (Reybroeck 2000a,b;Okerman et al 2004;Popelka et al 2005). Table 7 presented the combined results of a previous study carried out in 2003 and 2004 (64 samples actually containing antimicrobial residues) with the pilot study.…”
Section: Resultssupporting
confidence: 92%
“…Premi Õ Test has generally been compared to a reference method, focussing on a family of antimicrobials, such as beta-lactams, using spiked meat juice samples and incurred poultry muscle samples (Popelka et al 2005) or tetracyclines (Okerman et al 2004). The detection limits for various antimicrobials, calculated in spiked juice samples, were similar in the different studies.…”
Section: Introductionmentioning
confidence: 99%
“…Popelka et al [46] showed that Premi®Test exhibits excellent sensitivity for penicillin, amoxicillin, ampicillin, oxacillin, and cloxacillin. The study includes results of poultry muscle samples originating from animals treated with amoxicillin.…”
Section: Methods Developmentmentioning
confidence: 99%
“…A significant number of methods use precolumn derivatization techniques for fluorescence detection performed by reaction with TCA (20% w/v) aqueous solution and HCHO (7% w/v) [16,19,20] or for UV detection at 320 -345 nm by benzoic anhydride to acrylate aminopenicillins and 1,2,4-triazole/imidazole and mercury(II) chloride at alkaline media (pH l 9) at 60 -658C in order to form mercury mercaptide derivatives and thus achieve higher sensitivity [21 -24]. Mass spectroscopy and MS/MS are used for confirmation analysis [25 -28].…”
Section: Introductionmentioning
confidence: 99%
“…Deproteinization of the samples can be achieved by 5% Na 2 WO 4 and 0.33 N H 2 SO 4 [12,21,22], by 2% NaCl, 5% Na 2 WO 4 , and 0.17 M H 2 SO 4 [18], by Et 4 NCl [15,27], by ACN [16], by phosphate buffer (pH 8.5) and H 2 SO 4 [24] or 30% TCA [20]. Extraction of penicillins can be achieved by CH 2 Cl 2 , CH 3 CN, and hexane [29], H 2 O, CH 3 CN, and NaCl solution [26], 2% NaCl [17,26], HCOOH [30], ACN/H 2 O (30:70 v/v) [17,18,25,26], or by tert-butyl alcohol and water [15,16].…”
Section: Introductionmentioning
confidence: 99%